Changing perceptions and usage of public and pseudo-public spaces in the post-pandemic city: the case of Istanbul - Paköz, Muhammed Ziya; Sözer, Cansu; Doğan, Ayşen (Urban design international (London, England), 2022)
Public space has critical importance for the city and society because it forms a sense of community. The debate on the end of public space, which is ongoing as the privatization in the city rises, moves on to a new phase with the Covid-19 outbreak. Since the perception of public spaces will be a determinant factor in the future of the city, the question arises: How the perception and usage of the public, virtual public and pseudo-public spaces (particularly shopping malls) have been affected by the recent Covid-19 pandemic? The aim of this study is to examine the changing perception and usage of public and pseudo-public spaces during the Covid-19 outbreak in Istanbul, Turkey. Within this scope, an online survey was conducted with 337 participants living in Istanbul between the dates of 1–5 June 2020. With this survey, the change in perceptions and usage of these spaces based on personal, residential and district characteristics were investigated. The findings of the study revealed statistically significant differences between the perceptions and usage of public spaces and pseudo-public spaces before and after the Covid-19 outbreak in terms of personal, residential and district characteristics. According to survey results, there would be a significant decrease in the frequency of possible visits to public places. The outbreak reduces interest in virtual spaces as a leisure activity, but it also increases the interest in virtual spaces as a shopping and meeting/chat platform. In addition, it was determined that the demand for shopping centres and virtual platforms as both before-after-the-outbreak leisure activities decreased significantly as the amount of green space per capita increases. Besides, the diminishing reputations of pseudo-public spaces and the increasing importance of virtual public spaces may be observed from the survey results. The longer the outbreak, the greater its impact on the design and planning of public spaces and pseudo-public spaces. Rather than planning huge and crowded spaces such as big squares and huge malls, there is likely a shift toward planning a large number of small-scale public spaces within walking distance.